In vitro effect of josamycin in strains of Rhodococcus equi isolated from pulmonar infections in foals.
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Antmicrobial susceptibility test was performed in thirty-one samples of Rhodococcus equi isolated from iung infections in foals. Among the antimicrobial tosted, erythromycin (100,0 %), rifampin (96.3%). neomycin (93,6 %)Josamycin (90,4%) and gentamicin (90,4 %)presented the highest sensitivity against R- equi- The most-common occurrence of resistance was observed from cephalexim (100,0 %